Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1038/modpathol.2011.2
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and molecular characterization of nine cases of columnar cell variant of papillary thyroid carcinoma

Abstract: The majority of papillary thyroid carcinoma is indolent and associated with long-term survival. The columnar cell variant, however, is a rare subtype that is variable in biological behavior; some are clinically aggressive, whereas others are more clinically indolent. Tumor size, tumor circumscription, and encapsulation may influence the behavior of columnar cell carcinomas. Other variables including genetic changes and putative biomarkers associated with malignant growth have not been thoroughly examined in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 72 publications
0
70
1
6
Order By: Relevance
“…Chen et al have reported on the expression of BRAF V600E mutation in columnar cell carcinomas. In that study, three of nine columnar cell carcinomas exhibited this mutation and two of the three tumours had an aggressive behaviour 11. We tested two different blocks with columnar cell carcinoma, one of which had a KRAS p.G12D mutation and the other none.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al have reported on the expression of BRAF V600E mutation in columnar cell carcinomas. In that study, three of nine columnar cell carcinomas exhibited this mutation and two of the three tumours had an aggressive behaviour 11. We tested two different blocks with columnar cell carcinoma, one of which had a KRAS p.G12D mutation and the other none.…”
Section: Discussionmentioning
confidence: 99%
“…The columnar cell variant is believed by most to be a subtype of papillary carcinoma although some suggest that it is a distinct entity 1 11. Chen et al have reported on the expression of BRAF V600E mutation in columnar cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…[13] The prevalence of BRAF V600E mutations is less frequent with other aggressive variants as 33% in columnar cell variant, 50% in Hobnail variant, and absent in diffuse sclerosing variant. [141516]…”
Section: Introductionmentioning
confidence: 99%
“…The BRAF V600E mutation is found in about 33% of these tumors [Evans, 1986;Chen et al, 2011;Haugen et al, 2016].…”
Section: Molecular Alterations Associated With Aggressive Variants Ofmentioning
confidence: 99%